TEACHER'S TEACHING METHOD FOR INCLUSIVE STUDENTS USED IN ALAM MAHIRA SCHOOL BENGKULU - Gita Aprillasis; Fitri sugiarti (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the teaching methods used by teachers for inclusive children used in Mahira Alam School (SD, SMP, SMA) and how is the implementation of the inclusive teaching method used by student teachers at the Mahira Alam Bengkulu School. The type of research used in this research is qualitative research. The data collection technique used was direct observation at school. The subjects of this study were English teachers at Mahira Alam School (elementary, junior high, high school). The results of the study show that there are 4 teaching methods that the teacher uses in teaching inclusive students at the Alam Mahira Bengkulu School, namely; use of Direct Teaching Methods 92%, Indirect Teaching Methods 59%, Scaffolding 63%, Self-Training 74%. the teaching method is often used by teachers at the Alam Mahira school Direct Teaching Method and the method that is rarely used is Indirect Teaching Methods. Implementation of the teaching method by Teachers for inclusive students at the Alam Mahira School of Bengkulu Almost all the elements of teaching method for inclusive students at Alam Mahira Schools (SD, SMP, and SMA), namely the Direct teaching method by providing training with guidance, submission of materials and providing feedback. Indirect teaching method by means of the teacher as a facilitator and Student- centered learning. Self-training method by means of Facilitating Students to be able to work Self, Train students to practice a small number of skills, and Provide exercises so students can develop abilities. Scaffolding method by means of Set the difficulty level of the difficulty of the subject matter, utilize a variety of learning models, and Practice responsibility for future researchers, it is suggested that it can be used to find out student responses to the teaching methods used by several teachers in inclusive schools. Key Words: Inclusion, Teaching, Method